2016
DOI: 10.1007/s00345-016-1977-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased nucleophosmin expression is a strong predictor of recurrence and prognosis in patients with N0M0 upper tract urothelial carcinoma undergoing radical nephroureterectomy

Abstract: Increased nucleophosmin expression was a strong predictor of extraurothelial recurrence and cancer-specific survival in patients with N0M0 UTUC undergoing radical nephroureterectomy. Our risk stratification models integrating nucleophosmin expression may provide valuable information on disease recurrence and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Of these 442 proteins, 102 ( t ‐test <0·05) and 20 (B‐H adjusted t ‐test P < 0·05) proteins were differentially expressed between the two patient groups (all 102 are listed in Table SII) (Fig ). Sixty‐five proteins were overexpressed in the REF/REL group and several of these proteins (Elongation factor 1‐beta, 14‐3‐3 protein gamma, nucleophosmin 1, RAP1B, Heat shock protein 60 and IMP dehydrogenase 2) have previously been described as negative prognostic factors or involved in drug resistance in other malignancies (De Bortoli et al , ; Li et al , ; Raungrut et al , ; Zhou et al , ; Yang et al , ; Sawazaki et al , ). Two proteins overexpressed in the REF/REL group have been reported as a negative prognostic marker or associated with multidrug resistance in DLBCL: Y‐box protein 1 (Miao et al , ) and pontin/RuvBL1 protein (Nishiu et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these 442 proteins, 102 ( t ‐test <0·05) and 20 (B‐H adjusted t ‐test P < 0·05) proteins were differentially expressed between the two patient groups (all 102 are listed in Table SII) (Fig ). Sixty‐five proteins were overexpressed in the REF/REL group and several of these proteins (Elongation factor 1‐beta, 14‐3‐3 protein gamma, nucleophosmin 1, RAP1B, Heat shock protein 60 and IMP dehydrogenase 2) have previously been described as negative prognostic factors or involved in drug resistance in other malignancies (De Bortoli et al , ; Li et al , ; Raungrut et al , ; Zhou et al , ; Yang et al , ; Sawazaki et al , ). Two proteins overexpressed in the REF/REL group have been reported as a negative prognostic marker or associated with multidrug resistance in DLBCL: Y‐box protein 1 (Miao et al , ) and pontin/RuvBL1 protein (Nishiu et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22] Sawazaki et al reported that nucleophosmin is strongly associated with the recurrence and prognosis of urothelial carcinoma patients with radical nephroureterectomy. 23 Chen et al revealed that NPM1 inhibits apoptosis through its effects on Akt activity in breast cancer. 24 However, the upstream molecular mechanisms through which NPM1 promotes cancer progression remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…NPM expression predicts recurrence and survival in upper tract urothelial carcinoma. High NPM expression significantly correlates with tumor location [ 52 ]. NPM is a multifunctional oligomeric phosphoprotein and is encoded by the NPM1 gene [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%